Earnings Predictability of Quoted Firms in Nigeria - Olaniyi, Taiwo Azeez; Abogun, Segun; Salam, Mudathir Olanrewaju (Bangladesh Journal of Multidisciplinary Scientific Research, 2020)
The inability of investors to predict future earnings of firms exposes them to further risk such that potential investors may be scared away while existing ones may be prompted to withdraw their investment. Thus, it becomes imperative to evaluate the earnings predictability of Nigerian quoted firms with a view to establish the ability or inability of earnings to predict itself. Also, the study examined the impact of volatility on earnings predictability of Nigerian quoted firms. The total number of seventy three (73) quoted Nigerian firms constitutes the population of this study and the entire 73 firms were studied. The causal relationship research design was adopted. The secondary data used were collected from the financial statements of the quoted firms for the period 1996 to 2015. The system generalized method of moment (GMM) was used to estimate the dynamic panel regression models of the study. The study found that earnings of firms are predictable. The study also found that volatility has adverse effect on earnings predictability. It was therefore recommended more interest/investment in Nigerian firms since earnings information is available and is predictable while managements of firms should reduce instability in reported earnings.